Differential cellular responses induced by dorsomorphin and LDN‐193189 in chemotherapy‐sensitive and chemotherapy‐resistant human epithelial ovarian cancer cells. Issue 5 (26th September 2014) - Ali, Jennifer L.; Lagasse, Brittany J.; Minuk, Ainsley J.; Love, Allison J.; Moraya, Amani I.; Lam, Linda; Arthur, Gilbert; Gibson, Spencer B.; Morrison, Ludivine Coudière; Werbowetski‐Ogilvie, Tamra E.; Fu, Yangxin; Nachtigal, Mark W.
<x xml:space="preserve">Abstract</x> Inherent or acquired drug resistance is a major contributor to epithelial ovarian cancer (EOC) mortality. Novel drugs or drug combinations that produce EOC cell death or resensitize drug resistant cells to standard chemotherapy may improve patient treatment. After conducting drug tolerability studies for the multikinase inhibitors dorsomorphin (DM) and it is structural analogue LDN‐193189 (LDN), these drugs were tested in a mouse intraperitoneal xenograft model of EOC. DM significantly increased survival, whereas LDN showed a trend toward increased survival. In vitro experiments using cisplatin (CP)‐resistant EOC cell lines, A2780‐cp or SKOV3, we determined that pretreatment or cotreatment with DM or LDN resensitized cells to the killing effect of CP or carboplatin (CB). DM was capable of blocking EOC cell cycle and migration, whereas LDN produced a less pronounced effect on cell cycle and no effect on migration. Subsequent analyses using primary human EOC cell samples or additional established EOC cells lines showed that DM or LDN induced a dose‐dependent autophagic or cell death response, respectively. DM induced a characteristic morphological change with the appearance of numerous LC3B‐containing acidic vacuoles and an increase in LC3BII levels. This was coincident with a decrease in cell growth and the altered cell cycle consistent with DM‐induced cytostasis. By contrast, LDN produced a caspase 3‐independent, reactive oxygen species‐dependent cell death. Overall, DM and LDN possess drug characteristics suitable for adjuvant agents used to treat chemotherapy‐sensitive and ‐resistant EOC.